PEMBERDAYAAN MASYARAKAT UNTUK MEMAJUKAN UMKM MASA PANDEMI COVID-19 AIR TAWAR BARAT PADANG UTARA KOTA PADANG - Agustina, Yolanda (Education For All, 2022)
Many SMEs experienced a decline in income during the Covid-19 pandemic. This decrease is because there are restrictions for people to leave the house. The decline in people's purchasing power makes MSMEs think well to change their sales from direct to online. This is done in order to be able to continue the MSME business established. The goal is to get the right model and strategy to increase income during the Covid-19 pandemic. This observation uses a qualitative approach with the method of observation and interviews. The results of the observations show that some of the obstacles experienced by MSME actors during the time of covid-19. So that the most needed empowerment strategy for MSME actors is the empowerment of product innovation, product marketing and skills. By providing training and monitoring to MSME actors, it is hoped that MSMEs can increase income and solve problems that arise due to Covid-19.